2016
DOI: 10.22146/gamaijb.9285
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional and Rational Trust in Explaining Attitudinal and Behavioral Loyalty: An Insight Into SME Brands

Abstract: Brand trust is a powerful asset for Small and Medium size Enterprises (SMEs) to retain good relationships with their loyal customers, to ensure their long term survival. However, SME managers first need to understand the consequences of the two unique emotional and rational components of trust on attitudinal and behavioral loyalty, because both loyalty dimensions have unique consequences for a brand's performance. Hence, this study aims to answer two research issues: (1) Do brand intentions and brand reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…This fact shows that the better the transportation aspects of SMEs, the more positive impacts on the supply chain competitive strategy. These results are consistent with the studies of Ong, et al [10] and Kantari, et al [22]. Determination of suitable transportation routes and delivery of appropriate orders impacts customer service and loyalty.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This fact shows that the better the transportation aspects of SMEs, the more positive impacts on the supply chain competitive strategy. These results are consistent with the studies of Ong, et al [10] and Kantari, et al [22]. Determination of suitable transportation routes and delivery of appropriate orders impacts customer service and loyalty.…”
Section: Discussionsupporting
confidence: 92%
“…In other aspects, transportation, information, sourcing, and pricing also significantly affect the supply chain competitive strategy. The transportation aspect findings are consistent with the research conducted by Ong, et al [10] and Kantari, et al [22]. They explained that transportation has an impact on the supply chain's competitive strategy.…”
Section: Model Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The focus on loyalty has been increasing particularly due to inability of consumers to differentiate brands in certain product categories 59 . Despite the strategic importance of brand loyalty for brand managers 60, 61 , the topic is still debatable 62, 63 . For example, the dimensionality and definition of consumer loyalty has been debated extensively in academic literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the dynamics of entrepreneurial social capital, trust and commitment are also important aspects in maintaining business. Furthermore, Ong et al (2016) showed that consumer emotional and rational factors influenced trust and loyal behavior, so that imaging and product quality must be maintained for business continuity. In addition, the social and cultural aspects of society are also important to be integrated with the concept of entrepreneurship.…”
Section: Contribution Of the Development Of Regional Creative Industrmentioning
confidence: 99%